2010
DOI: 10.4081/or.2010.e23
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in secondary osteoarthritis: from cartilage destruction to clinical presentation?

Abstract: Due to an increasing life expectance, osteoarthritis (OA) is one of the most common chronic diseases. Although strong efforts have been made to regenerate degenerated joint cartilage, OA is a progressive and irreversible disease up to date. Among other factors the dysbalance between free radical burden and cellular scavenging mechanisms defined as oxidative stress is a relevant part of OA pathogenesis. Here, only little data are available about the mediation and interaction between different joint compartments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 88 publications
(85 reference statements)
1
59
0
1
Order By: Relevance
“…However, they certainly play important signaling roles in the process of osteoclastogenesis (21,22). Many previous studies have shown that ROS accumulation can increase the expression of RANKL in osteoclasts and enhance their survival and proliferation (19,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they certainly play important signaling roles in the process of osteoclastogenesis (21,22). Many previous studies have shown that ROS accumulation can increase the expression of RANKL in osteoclasts and enhance their survival and proliferation (19,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS can also cause bone destruction by exerting oxidative damage to all cellular biomolecules such as proteins, lipids and nucleic acids (21,22). In addition, the overproduction of ROS has been demonstrated to increase the expression of RANKL by osteoclasts, thereby activating osteoclasts and enhancing bone resorption capacity, indicating that ROS play an important role in osteoclastogenesis (19,23,24).…”
mentioning
confidence: 99%
“…Damaged mitochondria can lead to cell senescence and death. However, ROS generation has an important effect on the over-proliferation of PTKO and synovial membrane (23). Previous studies have suggested that ROS can regulate cell proliferation, differentiation, programmed cell death and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Τhese biomarkers are affecting the onset of OA, through the rise of levels of collagen type II, while increasing the expression of aggrecan and inhibit the apoptosis of proteins related to the protection of cartilage 46,47 . The MD components hydroxytyrosol, resveratrol and oleuropein show antioxidant action in vitro, as they constrain the activation of transcription NF-kB factors and AP-1 and decrease the expression of endothelial adhesion molecules 48 .…”
Section: Antioxidant Capacitymentioning
confidence: 99%